THE ROLE OF MUHAMMADIYAH IN THE FIELD OF EDUCATIONTHE LEADERSHIP PERIOD OF H. MISMAR MA'AHUIN KAMPAR DISTRICT: PERAN MUHAMMADIYAH DALAM BIDANG PENDIDIKAN MASA KEPEMIMPINAN H. MISMAR MA’AHU DI KABUPATEN KAMPAR - Fiona Rahmawati; Isjoni; Ahmal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Muhammadiyah is currently an influential organization in the world of education, even though it was initially founded by an Islamic group, Muhammadiyah has been able to develop well over time so that it is easily accepted by all elements of Indonesian society. To find out the role of educational institutions established by Muhammadiyah in advancing education in Kampar Regency, supervision will be carried out on these educational institutions, with the aim that existing Kampar Regency educational institutions can run according to their functions and can demonstrate their role to enrich the life of a nation. The aim of this research is to determine the initial process of Muhammadiyah's role in the field of education, to determine the process of Muhammadiyah's role in the field of education, to determine the impact of Muhammadiyah's role in the field of education. This research uses a type of historical or historical research that has four steps, Heuristics, Criticism, Interpretation, and Histiography. The research location is in Kampar Regency. From the results of this research, it can be seen the role of H. Mismar Ma'ahu in advancing education in Kampar Regency by establishing Muhammadiyah schools and contributing as a Muhammadiyah leader in education such as providing scholarship assistance for the people of Kampar Regency, and also developing the Muhammadiyah education curriculum. through Dikdasmen, which implements the mixed curriculum implemented in Muhammadiyah Muhammadiyah schools in Kampar Regency, it can be seen that there has been an increase in access to education during the H. Mismar Ma'ahu period. Through the establishment of schools and educational institutions in areas that were previously less accessible, Muhammadiyah has opened the door to education for the people of Kampar Regency to promote education with Islamic character and values.